2018
DOI: 10.1111/liv.13736
|View full text |Cite
|
Sign up to set email alerts
|

Mother‐to‐child transmission of hepatitis B: Examining viral cut‐offs, maternalHBsAg serology and infant testing

Abstract: Antiviral therapy initiated at 32 weeks when maternal viral load is ≥6 log IU/mL almost completely abrogates transmission. Quantitative HBsAg does not reliably predict high viral load. When maternal viral load is <6 log IU/mL, high vaccine efficacy and zero transmission suggests testing infants is of little value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 41 publications
2
15
0
Order By: Relevance
“…Therefore, pregnant women with HBV infection are prone to hepatitis attacks during pregnancy, resulting in significant damage to liver function, which can, not only cause protein synthesis disorders, hypoalbuminemia and anemia during pregnancy, increase the risk of infection, affect fetal growth and development but also cause abnormal coagulation function and increase the risk of bleeding during delivery [5] . In addition, severe liver damage can also cause the decrease of antidiuretic hormone, aldosterone and other inactivated ability, increase the risk of gestational hypertension and abnormal glucose metabolism [6] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, pregnant women with HBV infection are prone to hepatitis attacks during pregnancy, resulting in significant damage to liver function, which can, not only cause protein synthesis disorders, hypoalbuminemia and anemia during pregnancy, increase the risk of infection, affect fetal growth and development but also cause abnormal coagulation function and increase the risk of bleeding during delivery [5] . In addition, severe liver damage can also cause the decrease of antidiuretic hormone, aldosterone and other inactivated ability, increase the risk of gestational hypertension and abnormal glucose metabolism [6] .…”
Section: Resultsmentioning
confidence: 99%
“…This result suggests that telbivudine treatment has better antiviral and liver function protection effects than entecavir treatment in pregnant women with hepatitis. This is because telbivudine can compete with 5-triphosphate of HBV-DNA to inhibit HBV-DNA activity, thereby inhibiting HBV replication in vivo and reducing its damage to liver cells [9] . Some studies suggest that patients with HBV infection are mostly in immune disorder.…”
Section: Resultsmentioning
confidence: 99%
“…Intrauterine transmission, transmission during delivery, and transmission via breast milk and saliva are important routes for MTCT of HBV during pregnancy; thus, blocking these routes are of great importance to preventing MTCT of HBV, ensuring the safety of the mother and infants 8–10 . When pregnant women with HBV infection give birth, although active and passive immunity can be established using HBV vaccine, some neonates are infected via vertical HBV infection, leading to failure of the blockade 11, 12 . Studies have shown that HBV DNA is an important contributor to host infection, viral replication, and leads to the failure of active and passive immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Among the selected studies, 3 RCTs [7-9] and 12 non-RCTs [10,[16][17][18][19][20][21][22][23][24][25][26] compared treatment started in the third trimester versus control, 7 non-RCTs compared the timing of second trimester versus control [27][28][29][30][31][32][33], 3 non-RCTs compared first trimester versus control [14,34,35], 4 non-RCTs compared second and third trimester versus control respectively [11,[36][37][38], 3 non-RCTs compared first, second trimester versus control respectively [39][40][41]; 2 non-RCTs compared first, third trimester versus control respectively [12,42], 1 non-RCTs compared first, second trimester, third trimester versus control respectively [13]. No randomized controlled trials were conducted for the treatment that was applied during first or second trimester except for several non-RCTs.…”
Section: Characterization and Quality Of Studiesmentioning
confidence: 99%